Tìm đạo hàm của hàm số \(y=\dfrac{2x+5}{x^2+3x+3}\).
\(y'=\dfrac{2x^2+10x+9}{\left(x^2+3x+3\right)^2}\) | |
\(y'=\dfrac{-2x^2-10x-9}{\left(x^2+3x+3\right)^2}\) | |
\(y'=\dfrac{x^2-2x-9}{\left(x^2+3x+3\right)^2}\) | |
\(y'=\dfrac{-2x^2-5x-9}{\left(x^2+3x+3\right)^2}\) |
Chọn phương án B.
\(\begin{aligned}
y'&=\dfrac{(2x+5)'\left(x^2+3x+3\right)-(2x+5)\left(x^2+3x+3\right)'}{\left(x^2+3x+3\right)^2}\\
&=\dfrac{2\left(x^2+3x+3\right)-(2x+5)(2x+3)}{\left(x^2+3x+3\right)^2}\\
&=\dfrac{2x^2+6x+6-\left(4x^2+6x+10x+15\right)}{\left(x^2+3x+3\right)}\\
&=\dfrac{-2x^2-10x-9}{\left(x^2+3x+3\right)^2}.
\end{aligned}\)